Use of antisera to epithelial membrane antigen for the cytodiagnosis of malignancy in serous effusions. Issue 12 (December 1981) - To, A; Coleman, D V; Dearnaley, D P; Ormerod, M G; Steele, K; Neville, A M
Abstract : A new human antigen, designated epithelial membrane antigen (EMA), has recently been described on surface membranes of a wide variety of normal epithelium but not on connective tissue cells. The antigen is only weakly expressed on normal or reactive mesothelium. Increased expression of the antigen has been observed in most neoplasms of epithelial origin and in malignant mesothelioma. We have investigated the possibility of using this difference in the expression of the antigen to distinguish between mesothelial cells and malignant cells in cytological smears of serous effusions. This distinction cannot always be made on morphological grounds alone and problems of differential diagnosis are encountered in about 15% of all specimens of serous effusions sent for cytological examination. Using antisera to EMA we have applied an indirect immunoalkaline phosphatase technique to alcohol-fixed smears prepared from serous effusions and have found that intense staining of the antigen is confined to effusions from patients in whom there is either clinical or cytological evidence of malignancy. The technique proved to be especially useful in cytologically equivocal cases, where there were problems of differential diagnosis.